Opinions about Consumer Behavior during the Covid-19 Pandemic - Rafadi Khan Khayru (Journal of Social Science Studies (JOS3), 2021)
Consumer behavior is not just buying to meet needs and wants, but also includes the study of how involved decision-making processes and exchange processes and various things that affect individual and social life. The coronavirus pandemic is highly contagious and has spread rapidly and is happening globally. The spread of this disease outbreak has affected consumer behavior. The situation during the pandemic caused buying activities to change online. Consumers avoid physical contact to avoid transmission. In addition, panic buying occurred in several situations due to excessive anxiety from the public. This article reviews opinions on changes in consumer behavior during the Covid-19 pandemic. How consumers behave during the pandemic and the impact that occurs on shopping behavior in the post-pandemic.